Resonant tunneling diode optoelectronic integrated circuits - Ironside, Charlie; Figueiredo, J.; Romeira, B.; Slight, T.; Wang, L.; Wasige, E. (2010)
We present a review of Resonant Tunneling Diode (RTD) OptoElectronic Integrated Circuits (OEICs). Resonant tunneling diodes (RTDs) can be relatively easily integrated on the same chip as optoelectronic components and in this paper we discuss the integration of RTDs with laser diodes, electroabsorption modulators and photodiodes. The RTD provides the OEIC with negative differential resistance over a wide bandwidth. RTDs are highly nonlinear devices and by applying nonlinear dynamics we have recently gained considerable insight into the operation of the RTD OEICS and that has allowed us to design, fabricate and characterize OEICs for wireless/photonic interfaces. © 2010 Copyright SPIE - The International Society for Optical Engineering.